Dissolved organic matter characterization in a large arctic river : origins and dynamic - Le Dantec, Théo Aurélien (CCSD, 2018)
Arctic regions are expected to be highly sensitive to climate change regarding the prediction of disproportionately large increases in surface temperatures and their related influence over the hydrological cycle and permafrost thaw. These modifications have the potential to impact biogeochemical cycles in these regions and in particular the mobilization of organic carbon into rivers. The most crucial period in arctic rivers hydrological cycle is the spring freshet that can account for most of the annual organic carbon transfers to the ocean in a very short window of time. The focus of this thesis was to monitor the dynamic of DOM in terms of quantity and quality along the hydrological cycle of the Yenisei river, through DOM characterization approaches to reveal seasonal variations in its composition, sources, age and degradation state. The first step was to make a review of the full range of existing DOM characterization approaches in worldwide river systems to identify the most widely used, the most relevant and reliable ones. Through the development of a DOM quality measurements database, we have been able to evaluate the geographical coverage of DOM characterization studies, to give estimates and ranges of values of the main reported DOM characterization variables and to observe global trends of DOM quality across latitudinal gradient. Second stage was to investigate DOC dynamic in the Yenisei river with regard to quantity and links with water chemistry and hydrology. We conducted sampling campaigns during three consecutive years (2014 to 2016), covering with a high sampling frequency the spring flood period to capture its very dynamic evolution. We reported DOC concentrations that followed the hydrograph with highest concentrations observed a few days before peak discharge. DOC concentration also responded to discharge variation (increase, likely due to higher precipitation) in early autumn. We reported average DOC flux over the three sampling years of about 4.53 Tg yr-1 which is within the range of values ...